Diskriminasi Pembelajaran Online pada Sekolah Swasta - Mulyani Mudis Taruna; Abdul Rohman (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2021)
The Covid-19 pandemic that has hit the world, including Indonesia, has prompted changes in education policy, from a face-to-face model to a distance learning model. Distance learning through online media has generated a lot of educational discrimination. Schools in urban areas are generally able to design online learning well because they are supported by smartphone facilities owned by all students and the ease of internet networks. However, in rural schools, online learning is quite tricky because not all students have smartphones and internet network problems. This study aims to determine the implementation of learning during the Covid-19 Pandemic in private schools. This research is qualitative research with a case study approach with cyclic analysis at the Junior High School of Muhammadiyah Tonjong. This study found that online learning during the Covid-19 pandemic made the world of education experience discrimination. Online learning at the Junior High School of Muhammadiyah Tonjong during the Covid-19 Pandemic ran without structured planning, and incomplete smartphone devices make learning ineffective. It causes the quality of students in the mastery of teaching materials is less than optimal and reduces student achievement. Optimization of online learning activities is carried out by assigning individual and group assignments to all students. In practical learning, students are requested to make videos in groups.